Initiation of anticoagulation in atrial fibrillation by primary care physicians: Results of a telephone survey. Issue 202 (June 2021) - Carlin, Stephanie; Bond, Alison; Gross, Peter; Bell, Alan; Douketis, James; Geerts, William; Galanaud, Jean-Philippe
Abstract: Background: Direct oral anticoagulants (DOACs) are prescribed for over 80% of patients who start anticoagulant therapy for a new diagnosis of atrial fibrillation (AF). Inappropriate DOAC prescriptions are associated with increased mortality. However, limited data exist as to what proportion of primary care physicians (PCPs) initiate anticoagulation in patients with new AF and the extent of their DOAC knowledge. Material and methods: We conducted a telephone survey of randomly selected PCPs in Ontario, Canada. Our primary objective was to determine the percentage of PCPs who initiate anticoagulation in new AF patients and the proportion of patients they initiate on DOACs. Our secondary objectives were to assess PCPs' knowledge about DOACs and to identify educational opportunities to address any knowledge gaps. Results: Our survey included 50 respondents. After making a new AF diagnosis, 66% of PCPs stated that they usually initiate anticoagulation themselves and 84% prescribed a DOAC at least 75% of the time. Potential DOAC knowledge gaps included: administration considerations, off-label dosing, concomitant use of acetylsalicylic acid (ASA) in stable coronary artery disease (CAD) and use in valvular AF. Conclusion: Most PCPs initiate anticoagulants for AF and prescribe DOACs for the vast majority of new patients. PCPs were well versed in certain aspects of DOAC prescribing, however, a number of knowledge gaps were identified. PCPs may benefit from targeted education in these areas to improve patient outcomes in AF. Highlights: Most primary care physicians self-initiate anticoagulation in patients with atrial fibrillation. Most primary care physicians prescribe direct oral anticoagulants over warfarin. Direct oral anticoagulant knowledge gaps exist among primary care physicians.